One amazing thing - Divakaruni, Chitra Banerjee, 1956- (New York : Voice/Hyperion, 2010)
When nine disparate characters are trapped together after an earthquake, each of them takes a turn telling "one amazing thing" about his or her life.
Keywords: Earthquakes -- California -- Fiction; East Indians -- California -- Fiction; Disaster victims -- Fiction; Storytelling -- Fiction; California -- Fiction; Psychological fiction